2015
DOI: 10.1073/pnas.1414841112
|View full text |Cite
|
Sign up to set email alerts
|

RNA transcribed from a distal enhancer is required for activating the chromatin at the promoter of the gonadotropin α-subunit gene

Abstract: Since the discovery that many transcriptional enhancers are transcribed into long noncoding RNAs termed "enhancer RNAs" (eRNAs), their putative role in enhancer function has been debated. Very recent evidence has indicted that some eRNAs play a role in initiating or activating transcription, possibly by helping recruit and/or stabilize binding of the general transcription machinery to the proximal promoter of their target genes. The distal enhancer of the gonadotropin hormone α-subunit gene, chorionic gonadotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 48 publications
7
98
0
Order By: Relevance
“…Several studies reported recently that enhancer RNAs (eRNAs) are involved in transcriptional regulation of nearby coding genes (Lam et al, 2013, Kim et al, 2010, Melo et al, Lai et al, 2013, Mousavi et al, 2013, Hsieh et al, 2014, Schaukowitch et al, 2014, Pnueli et al, 2015, Zhao et al, 2016, Li et al, 2013). For instance, estrogen-induced eRNAs from ERα-bound active enhancers were critical for the transcriptional activation of cognate estrogen-induced coding genes (Li et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported recently that enhancer RNAs (eRNAs) are involved in transcriptional regulation of nearby coding genes (Lam et al, 2013, Kim et al, 2010, Melo et al, Lai et al, 2013, Mousavi et al, 2013, Hsieh et al, 2014, Schaukowitch et al, 2014, Pnueli et al, 2015, Zhao et al, 2016, Li et al, 2013). For instance, estrogen-induced eRNAs from ERα-bound active enhancers were critical for the transcriptional activation of cognate estrogen-induced coding genes (Li et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…eRNAs have been defined as short transcripts (50–2000 nucleotides) that are transcribed bi-directionally, or sometimes uni-directionally, from enhancer regions (Kim et al, 2010). Although whether eRNAs themselves are functional remains to be unequivocally proven, many studies have clearly demonstrated that enhancer transcription occurs before coding gene activation and may help to create an open chromatin environment, facilitate promoter and enhancer looping, and contribute to coding gene transcriptional regulation (Hsieh et al, 2014, Lai et al, 2013, Lam et al, 2013, Melo et al, 2013, Mousavi et al, 2013, Schaukowitch et al, 2014, Pnueli et al, 2015, Zhao et al, 2016, Li et al, 2013). In addition, enhancer transcription has been suggested to play an essential role in enhancer marker (H3K4me1/2) deposition at de novo enhancers (Kaikkonen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SEs are thought to signal to proximal promoters to stabilize BRD4-containing coactivator complexes near TSSs, thereby facilitating p-TEFb-mediated Pol II phosphorylation and transcription elongation (Arner et al, 2015; Brown et al, 2014; Pnueli et al, 2015). ChIP-Seq data were further analyzed to assess whether PE and/or miR-9 alter BRD4 binding to cardiomyocyte gene promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancer RNAs are expressed in a signal-dependent manner [80], and regulate gene expression via decondensing chromatin at target promoters, facilitating Pol II recruitment to TSSs of target genes, and promoting direct enhancer/promoter interaction through chromatin looping [8185]. In keeping with this model, genes that are acted upon by multiple eRNAs have significantly higher expression than eRNA-independent genes [84].…”
Section: Acetyl-lysine Readers and Fibrosismentioning
confidence: 99%